Multilateral diplomacy and the economics of change - Benn, Denis (Ian Randle KingstonJM, 2003)
Traces the evolution of the developing countries as actors in the economic system. Describes the circumstances which gave rise to the New International Economic Order (NIEO). Presents a detailed analysis of the negotiations on the NIEO and compares the strategies adopted by the parties to the negotiations. Describes the geopolitical context within which the negotiations were carried out. Highlights the role of South-South cooperation as a counter strategy pursued by the developing countries in order to strengthen their bargaining position.